TEACHERS' VIEWS ON THE MODEL OF STUDENT'S LANGUAGE PORTFOLIO IN ENGLISH LANGUAGE TEACHING AND LEARNING - Mutia Rahmadani; Yanto Yanto (JAMBI-ENGLISH LANGUAGE TEACHING, 2022)
The objective of this research is to explore the teachers’ views toward the model of student’s language portfolio in English language teaching and learning. Participants of this research included six lecturers in English Education Study Program at Universitas Jambi who teach language skills and had implemented portfolio in their respective class. A qualitative research design was employed by conducting interview with the participants as the primary data as well as document analysis as the secondary data for this research. The result of this research indicates portfolio is used in English Education Study Program at Universitas Jambi although it is not broadly implemented. The finding shows portfolio is developed according to two distinctive purposes, namely process and product portfolio with the tendency towards process portfolio in its implementation. The participants disclosed that the core components of portfolio include collection of students’ learning artifacts, result of peer review, and reflection which considered crucial to bring about effective record of student’s progress in learning. In it’s practice, portfolio implemented in accordance to project-based class within the purpose to encourage the students to work collaboratively in developing portfolio. Portfolio assessment decision is determined by the implementation of holistic assessment and the use of rubrics. Besides, peer review is employed in the assessment process in order to reduce teachers’ work for providing feedback towards students’ portfolio even though it is not accompanied by any scoring guidelines in its implementation.